Digital Economic Transformation on People's Consumption Patterns - Rio Rinaldy; Nur Syahrani Setiawati (Jurnal Ekonomi Teknologi dan Bisnis (JETBIS), 2026)
The digital economic transformation has transformed various aspects of people's lives, including consumption patterns. Developments in information technology, the internet, and digital platforms have driven changes in the way people search for, compare, and purchase goods and services. This study aims to analyze the impact of the digital economic transformation on changes in people's consumption patterns. The study used a qualitative approach with descriptive methods. Data were obtained through literature studies, observations of digital economic activities, and secondary data analysis from official reports and related publications. The results show that the digital economic transformation has driven a shift in consumption patterns from conventional to digital, characterized by increased use of e-commerce, non-cash payments, and a preference for ease and speed of transactions. Furthermore, the digital economy also influences impulsive consumption behavior and increases purchasing power based on technology access. This study concludes that the digital economy plays a significant role in shaping the consumption patterns of modern society and requires adaptive policies to support consumer protection and economic sustainability.